Energy use, health, and sleep in a bioclimatic university residence: a case study from 20 years of use - Filippin, Maria Celina (2024)
While recent studies have extensively explored energy consumption and conservation in students’ residences, research into thermal comfort, health conditions, and sleeping comfort in these settings remains limited, especially over extended durations. In this study, we present and discuss insights gleaned over 20 years (2001–2021) on the thermal and energy behaviors of Universidad Nacional de La Pampa’s bioclimatic student residences in Argentina. The building, drawing on 20 years of measured and simulated data, reveals promising heating energy savings while maintaining indoor ambient comfort. Across the 2001–2021 period, heating energy consumption averaged 109 kWh/m2/year, representing a 33% saving compared to conventional apartment block buildings in the same region. Our findings underscore the challenges of passive design during extreme heat, with summer temperatures exceeding comfort thresholds in buildings lacking air conditioning. A deeper analysis reveals discomfort percentages of approximately 15% (night) and 32% (nap) during sleeping periods, escalating up to 80% during heat waves. These findings echo concerns about overheated spaces in bioclimatic buildings across central Argentina, highlighting the imperative for effective summer cooling strategies. Through measurement data and simulations, this study illuminates the complex interplay among building design, environmental conditions, and occupant comfort, offering valuable insights for sustainable design and management practices.